PENERAPAN PENDIDIKAN KARAKTER SEBAGAI UPAYA MENGEMBANGKAN IMAN KRISTIANI PADA PESERTA DIDIK DI SMPK SANTO YUSUF MADIUN - Imeldasari, Magdalena Vivi; Permana, Natalis Sukma (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
Character education is an educational program that instills good values. The development of the times has hurt the development of students' faith, this shows the failure of character education programs for students so families, communities, and schools must be made aware again of how important character education is for students. Many students are mired in negative things such as smoking, skipping classes, consuming alcohol and drugs, and even entangled in free sex. The purpose of this study was to determine the role of character education in the development of students' faith, efforts to implement character education that can develop Christian faith, and find out the factors that influence the development of students' faith. This study used a descriptive qualitative method, and data collection techniques were carried out using observation, interview, and documentation methods on 5 students and 2 teachers at SMPK Santo Yusuf Madiun. The results showed that the informants understood the role of character education as an effort to develop Christian faith. Character education is provided to provide character insight, understand moral values, and shape the personality of students. Efforts are made through habituation activities such as morning prayer, meditation, student mass, recollection, and other activities. Factors supporting the development of students' faith are parents, school activities, and supporting spiritual facilities. Inhibiting factors usually come from student awareness, social environment, and background.